Improving the Luminescent Properties of Atomic Layer Deposition Eu:Y2O3 Thin Films through Optimized Thermal Annealing. Issue 8 (9th March 2020) - Scarafagio, Marion; Tallaire, Alexandre; Chavanne, Marie-Hélène; Cassir, Michel; Ringuedé, Armelle; Serrano, Diana; Goldner, Philippe; Ferrier, Alban
Abstract : Crystalline rare‐earth (RE)‐doped Y2 O3 films are an attractive system for a wide range of photonics applications including quantum technologies which aim at harnessing optical or spin transitions with long coherence times to achieve new functionalities such as quantum storage or information processing. Herein, atomic layer deposition (ALD) of Eu‐doped Y2 O3 thin films with improved optical properties is presented. A crucial post‐treatment step to obtain high‐quality films is annealing at elevated temperatures (>900 °C). However, the main drawback of this approach is the formation of unwanted parasitic phases due to reaction at the interface with the substrate, especially with silicon. In this article, this issue is discussed for different kinds of substrates and buffer layers. The use of such modified substrates allows advantageously extending the maximum thermal treatment up to 1150 °C without being limited by interface reactions. It is demonstrated that the emission of the 5 D0 → 7 F2 transition for Eu 3+ in Y2 O3 film can be as narrow as that of bulk materials when optimized thermal treatments and a thin undoped Y2 O3 buffer layer are used. Thus, a versatile method to reduce the impact of the substrate–film interface on the optical properties is proposed. Abstract : Rare‐earth‐doped oxide materials are attracting a wide interest for quantum technologies due to their ultralong optical and spin coherence times. Thin films of Eu:Y2 O3 grown by atomic layer deposition have photoluminescence emission as narrow as that of a bulk material, providing annealing at high temperature ( T > 900 °C) is conducted on an adapted substrate.